2018
DOI: 10.21037/jtd.2018.10.52
|View full text |Cite
|
Sign up to set email alerts
|

Circulating exosomal miR-92b-5p is a promising diagnostic biomarker of heart failure with reduced ejection fraction patients hospitalized for acute heart failure

Abstract: Background: Circulating microRNA (miRNA) biomarkers have been extensively reported in cardiovascular diseases (CVDs). However, serum exosomal miRNA (exo-miRNA) as biomarker in patients with heart failure (HF) with reduced ejection fraction (HFrEF) remain largely unexplored. We sought to investigate the potential of three types of serum exo-miRNAs as biomarkers for diagnosis in HFrEF patients who were admitted in hospital because of acute heart failure (AHF). Methods: A total of 28 HFrEF patients hospitalized f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
50
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 51 publications
(51 citation statements)
references
References 49 publications
0
50
0
1
Order By: Relevance
“…Similarly, another study was also shown that the serum level of Exo‐miR‐92b‐5p is significantly increased in HF with reduced ejection fraction (HFrEF) patients 138 . The levels of the serum Exo‐miR‐92b‐5p could discriminate HFrEF patients from healthy subjects with high sensitivity and specificity 138 .…”
Section: Potential Circulating Exo‐mir Biomarkers In the Diagnosis Of Hfmentioning
confidence: 94%
See 4 more Smart Citations
“…Similarly, another study was also shown that the serum level of Exo‐miR‐92b‐5p is significantly increased in HF with reduced ejection fraction (HFrEF) patients 138 . The levels of the serum Exo‐miR‐92b‐5p could discriminate HFrEF patients from healthy subjects with high sensitivity and specificity 138 .…”
Section: Potential Circulating Exo‐mir Biomarkers In the Diagnosis Of Hfmentioning
confidence: 94%
“…139 Similarly, another study was also shown that the serum level of Exo-miR-92b-5p is significantly increased in HF with reduced ejection fraction (HFrEF) patients. 138 The levels of the serum Exo-miR-92b-5p could discriminate HFrEF patients from healthy subjects with high sensitivity and specificity. 138 Analysis of echocardiographic data revealed that the serum level of Exo-miR-92b-5p is negatively correlated with the function of the left ventricle, whereas it is positively correlated with dilation of the left ventricle.…”
Section: Circulating Exo-mir-92b-5p In Dcm-ahf and Hfrefmentioning
confidence: 97%
See 3 more Smart Citations